Pengaruh Pengembangan Karir Dan Motivasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada Rumah Sakit Islam Metro) - Nina Lelawati; Jati Imantoro; Putri Pebianti (Universitas Muhammadiyah Metro, 2024)
Based on sources from the General Section and HR of the Metro Islamic Hospital, every 3-5years Exchange occupations are held. Employees whose skills or expertise have improvedafter attending regular career development trainings need to get appreciation, recognitionand promotion from the institution and the work environment. It encourages the employees’activeness and productivity in carrying out their works. The purpose of this study was to findout whether career development affected employee performance, whether motivation affectedemployee performance, whether career development affected job satisfaction, whethermotivation influenced job satisfaction, whether career development and motivation affectedemployee performance with job satisfaction as an intervening variable. The sample of thisresearch were 42 employees of Metro Islamic Hospital. Data collection used a questionnaire,and data analysis used a Validity Test, Reliability Test, Normality Test, Homogeneity Test,Linearity Test and Variable Regression Analysis with the Causal Step Method with the program (SPSS 25). The result of this study showed that there was a positive and significantinfluence of career development on employee performance. There was a positive andsignificant effect of motivation on employee performance. There was a positive andsignificant influence of career development on employee job satisfaction. There was apositive and significant influence of motivation on job satisfaction. There was a positive andsignificant influence of career development and motivation on employee performance withjob satisfaction as an intervening variable